PERBANDINGAN PERBEDAAN HASIL UJIAN OSCE SEMESTER 4 ANTARA METODE PEMBELAJARAN TATAP MUKA (LUAR JARINGAN) DAN DALAM JARINGAN (DARING) PADA MAHASISWA ANGKATAN 2017 DAN 2018 FK UMSU - YUSMALIZA MARPAUNG (LP2MTBM MAKARIOZ, 2023)
During the outbreak of the COVID-19 Virus pandemic at the beginning of 2020, all community activities were temporarily suspended and only allowed to do from home. So, All educational activities are carried out online. Of course, this has a big impact on the medical student learning system, which mostly uses face-to-face practices such as basic clinical skills and the implementation of OSCE. This research use an analytic study with cross sectional data. The sample of this study are FK UMSU students class of 2017 and 2018. The study used two-proportion difference test (z test). Based on the results of the z test calculation using the excel application, it was found that the z count was 0.252 with z alpha of 1, 644 then h0 failed to be rejected, there is no difference in the results of the OSCE exam before online learning in the 2017 class and after online learning in the 2018 batch at FK UMSU